The Development of Mathematical Performance From Kindergarten to Grade 1: The Role of Children's Mathematical Liking and Parents' Beliefs and Activities - Silinskas, Gintautas; Bourque, Taeko; Susperreguy, Maria Ines; Lefevre, Jo-anne; Raiziene, Saule (Wiley, 2026)
The transition from kindergarten to formal schooling is an important period for examining children's developing mathematical performance. We studied reciprocal associations among children's mathematical performance, parent factors (i.e., numeracy activities, beliefs about children's mathematical skills), and child factors (i.e., mathematics liking). Lithuanian children (N = 341; 180 girls) and their parents participated at three time points: end of kindergarten (T1; M-age = 6.87 years), beginning of Grade 1 (T2), and end of Grade 1 (T3). Reciprocal cross-lagged associations between parent- and child-related factors showed that children's mathematical performance positively predicted parental beliefs [beta(T1-T2) = 0.247, beta(T2-T3) = 0.280] and negatively predicted numeracy activities [beta(T1-T2) = -0.227, beta(T2-T3) = -0.110] during the transition from kindergarten to Grade 1, and during Grade 1. Children's mathematical performance positively predicted their mathematics liking at the end of Grade 1 (beta(T2-T3) = 0.138). The results emphasise the role of children's mathematical performance in shaping parents' involvement and beliefs about children's mathematical learning and their children's mathematics liking.